Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

whats the answer for y=-[tex]\frac{2}{3}[/tex]x+4 and y=[tex]\frac{1}{3}[/tex]x-2

Sagot :

corm

Step-by-step explanation:

[tex]y = -\frac{2}{3}x + 4[/tex]

[tex]y = \frac{1}{3}x - 2[/tex]

Since both equations are set equal to [tex]y[/tex], we can take the right-hand side of each equation and set them equal to each other to solve for [tex]x[/tex]:

[tex]-\frac{2}{3}x + 4 = \frac{1}{3}x - 2[/tex]

[tex]-\frac{2}{3}x - \frac{1}{3}x = -2 - 4[/tex]

[tex]-x = -6[/tex]

[tex]x = 6[/tex]

Now we can plug this value into either equation to solve for [tex]y[/tex]:

[tex]y = \frac{1}{3}x - 2[/tex]

[tex]y = \frac{1}{3}(6) - 2[/tex]

[tex]y = 2 - 2[/tex]

[tex]y = 0[/tex]

So the solution to the system of equations is [tex](6, 0)[/tex]